5G for future wireless networks : second EAI International Conference, 5GWN 2019, Changsha, China, February 23-24, 2019, Proceedings /: second EAI International Conference, 5GWN 2019, Changsha, China, February 23-24, 2019, Proceedings. (2019) - Unknown
No abstract available